ANALISIS KADAR LOGAM BERAT TIMBAL (PB) DAN CADMIUM (CD) PADA IKAN DEMERSAL DI TEMPAT PELELANGAN IKAN KABUPATEN LAMONGAN - Aryani, Amalia Dwi; Rahmiati, Retnani; Handarini, Kejora; Hariyani, Nunuk (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
Demersal fish live on the bottom of rocky, sandy, muddy, and craggy ocean with low mobility. Heavy metals settle to the bottom of waters since they have a greater specific gravity than seawater, resulting in a greater chance of entering the body of fish through the food chain process so that they can accumulate. This study aims to analyse the levels of heavy metals lead (Pb) and cadmium (Cd) in the liver, kidney, and meat organs of demersal fish in Lamongan Regency. Descriptive research with purposive sampling method is employed in this research. Analysis of heavy metal levels was conducted using a UV-Vis Spectrophotometer. The maximum limit of lead and cadmium in SNI 2729:2013 is 0.3 mg/kg and 0.1 mg/kg. Liver, kidney, and meat organs in 10 demersal fish species were positive for lead contamination, yet the levels did not exceed the limit. Liver, kidney, and meat organs in 10 types of demersal fish were positively contaminated with cadmium; in meat, there was 1 type of fish (10%) exceeding the limit, namely kuniran fish at 0.170 mg/kg; in the liver, there were 5 types of fish (50%) exceeding the limit, namely senangin fish at 0.124 mg/kg, swanggi fish at 0.129 mg/kg, spiny fish at 0.116 mg/kg, snapper fish at 0.103 mg/kg, and stingray at 0.101 mg/kg; and in the kidney, there were 4 fish species (40%) exceeding the limit, namely grouper at 0.169 mg/kg, kuniran fish at 0.129 mg/kg, kurisi fish at 0.117 mg/kg, and spiny fish at 0.109 mg/kg